Generic outcome set for the international registry on Laser trEAtments in Dermatology (LEAD): a protocol for a Delphi study to achieve consensus on what to measure. Issue 6 (28th June 2020) - Fransen, Frederike; Spuls, Phyllis; Alam, Murad; Badawi, Ashraf; Boixeda, Pablo; Haedersdal, Merete; Hamzavi, Iltefat; Hedelund, Lene; Kelly, Kristen M; Kono, Tara; Laubach, Hans Joachim; Manuskiatti, Woraphong; et al.
Abstract : Introduction: While laser technology has expanded the armamentarium of treatment for various skin diseases during the past years, heterogeneity in study outcomes hampers comparability and appropriate evidence synthesis. Part of these issues can be addressed by developing a generic outcome set. Using the Delphi method, this study aims to seek consensus between key stakeholders on relevant generic outcomes ( what to measure) for implementation in the international registry on Laser trEAtments in Dermatology (LEAD). The registry is focused on collecting research data on various laser treatments for skin disorders. Methods and analysis: By reviewing the literature and involvement of key stakeholder groups and adult patients in need or after laser surgery and health professionals, a preliminary list of outcomes will be generated and categorised into domains. Using these outcomes, an international three-round Delphi study will be performed to rate the importance of outcomes in the selection of a generic outcome set. Participants are allowed to provide new outcomes to the preliminary list for revisions during the first Delphi round. Finally, results will be discussed during a consensus meeting to agree on generic outcomes to be used in the LEAD registry. Ethics and dissemination: An ethics approval was not applicable (W19_290 # 18.336). The study is registered with the Cochrane Skin Core OUtcome Set INitiative) and the Core Outcome Measures in Effectiveness Trials initiative. Procedures will be conducted according to the Declaration of Helsinki. The findings will be disseminated through peer-reviewed publications and conference presentations.